2009
DOI: 10.1143/jjap.48.03b018
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Amorphous Indium Gallium Zinc Oxide Thin Film Transistors under Light Illumination

Abstract: The electrical and optical properties of amorphous indium gallium zinc oxide (a-IGZO) thin films and thin film transistors (TFTs) were investigated for their applications in flat panel displays (FPD). The device characteristics were found to be sensitive to gate dielectric and interlayer film material. TFTs using SiO 2 as a gate dielectric and passivation showed very good characteristics when measured in the dark, with mobility above 10 cm 2 V À1 s À1 , on/off ratio of %10 8 , sub-threshold swing less than 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…10 Thin-film transistors made of amorphous oxide semiconductors exhibit a variety of metastable changes in their transistor characteristics through carrier doping and optical [11][12][13] or electrical [14][15][16][17][18][19][20][21] (or both [21][22][23][24][25][26][27][28] ) excitation of carriers. Indium (In)-based amorphous oxide semiconductors are considered as a promising material for next-generation thin-film electronics and optoelectronics because they have high electron mobility, transparency, flexibility and uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thin-film transistors made of amorphous oxide semiconductors exhibit a variety of metastable changes in their transistor characteristics through carrier doping and optical [11][12][13] or electrical [14][15][16][17][18][19][20][21] (or both [21][22][23][24][25][26][27][28] ) excitation of carriers. Indium (In)-based amorphous oxide semiconductors are considered as a promising material for next-generation thin-film electronics and optoelectronics because they have high electron mobility, transparency, flexibility and uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, reports have indicated that visible illumination leads to electrical instability. For example, Takechi et al 6 and Gosain et al 7 both report a negative ⌬V T in In-Ga-Zn-O ͑IGZO͒ TFTs when illuminated with wavelength ͑͒ ϳ311 nm and Ͻ420 nm, respectively. The former attributed the negative ⌬V T in unpassivated devices to light-induced oxygen interstitials, while the latter ascribed it in passivated devices to hole trapping at light-created defects at interfaces.…”
mentioning
confidence: 99%
“…Such mechanisms do not exist in AOSs because of their ionic bonding [12]. However, the amorphous oxide TFTs do suffer from instabilities [9,[33][34][35][36]. We assume their surfaces are passivated, to avoid O 2 effects.…”
Section: Instabilitiesmentioning
confidence: 99%
“…A more important instability is under negative bias stress, under illumination [33][34][35][36]. Without illumination, there is little V T shift.…”
Section: Instabilitiesmentioning
confidence: 99%